A base-promoted cascade reaction of α, β-unsaturated N-tosylhydrazones with o-hydroxybenzyl alcohols: highly regioselective synthesis of N-sec-alkylpyrazoles. Issue 37 (12th September 2019) - Chen, Lian-Mei; Zhao, Juan; Xia, An-Jie; Guo, Xiao-Qiang; Gan, Ya; Zhou, Chuang; Yang, Zai-Jun; Yang, Jun; Kang, Tai-Ran
Abstract : An efficient method for the synthesis of N-sec -alkylpyrazoles via a cascade reaction of α, β-unsaturated N -tosylhydrazones with ortho -hydroxybenzyl alcohols has been developed. Abstract : An efficient method for the synthesis of N-sec -alkylpyrazoles through a base-promoted cascade cyclization/Michael addition reaction of α, β-unsaturated N -tosylhydrazones with ortho -hydroxybenzyl alcohols has been developed. The desired products containing di- or triaryl groups at the same carbon atom were afforded in good to excellent yields with excellent regioselectivities (>20 : 1). Moreover, a three-component reaction of ortho -hydroxybenzyl alcohols, α, β-unsaturated N -tosylhydrazones and saturated N -tosylhydrazones also took place to afford pyrazoles in good yields. This reaction offers a new route to triarylmethanes with a simple operation and is applicable for large-scale synthesis.